2020
DOI: 10.3390/ani10020328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Crude Protein on Productive Efficiency, Nutrient Digestibility, Blood Metabolites and Gastrointestinal Immune Markers in Light Lambs

Abstract: This study hypothesized that reducing the level of crude protein (CP) in lambs′ feed may improve nutrient utilization and did not negatively affect their productive efficiency, blood metabolites, oxidative status (OS) or intestinal immune barrier function. A total of 120 weaned male Ripollesa lambs (45–60 days old and 15.0 ± 1.5 kg of body weight) were used. Four feed concentrates were formulated for two different phases (growing and finishing): CP20/19 group (20% and 19% of CP on dry matter basis, for each ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It can be said that the decreases observed intra-group ALP values are related to the decrease in the amount of TP in the blood (Fig 1, panel C,G), protein uptake in the tissues and nitrogen evaluability (Dayıoğlu and Doğru, 1996). It has been stated that feeding a diet containing 17-20% crude protein after the weaning period does not affect the total MDA levels in male lambs (Pelegrin-Valls et al, 2020). An increase was observed in the MDA level of the MD group in the 2 nd and the 5 th period, while a decrease was observed in the transition to the 3rd period (P0.05) (Fig 1 , panel H).…”
Section: Intra-group Biochemical Parametersmentioning
confidence: 85%
“…It can be said that the decreases observed intra-group ALP values are related to the decrease in the amount of TP in the blood (Fig 1, panel C,G), protein uptake in the tissues and nitrogen evaluability (Dayıoğlu and Doğru, 1996). It has been stated that feeding a diet containing 17-20% crude protein after the weaning period does not affect the total MDA levels in male lambs (Pelegrin-Valls et al, 2020). An increase was observed in the MDA level of the MD group in the 2 nd and the 5 th period, while a decrease was observed in the transition to the 3rd period (P0.05) (Fig 1 , panel H).…”
Section: Intra-group Biochemical Parametersmentioning
confidence: 85%
“…On another note, creatinine is a byproduct of muscle metabolism and is excreted by glomerular filtration; thus, it can be used as an indicator of renal function (Thiet et al 2022 ). Moreover, blood urea is considering to be an indicator of ingested or mobilized protein (Pelegrin-Valls et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported that CP content of lamb feed can be reduced (10% below the current commercial standards) without a negative effect on growth performance or carcass yield of local Spanish breeds [ 16 ]. However, the impact of a reduction in the amount of dietary protein on metabolism should be carefully evaluated and adequate methods are needed, as many metabolic processes in mammals have been described as being influenced by eating frequency [ 18 ], which could impair the proper metabolic synthesis of proteins, and consequently, the growth of lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Before the experiment started, lambs were fed standard commercial diets for five days adaptation concentrate containing coccidiostatic (decoquinate at 30 mg/kg). Ingredients and chemical composition of the experimental diets can be found in Pelegrin-Valls et al [ 16 ], and the organic matter (OM), CP, P and AIA contents are reproduced in Table 1 . Briefly, pelleted diets were isoenergetic (1760 kcal of Net Energy for Ruminants/kg of concentrate) and they were formulated with the same ingredients and additives in the same manufacturing batch.…”
Section: Methodsmentioning
confidence: 99%